PERLINDUNGAN LUMBA-LUMBA SEBAGAI SATWA LANGKA YANG DILINDUNGI DARI TINDAKAN PENEMPATAN DAN ATRAKSI HIBURAN YANG TIDAK SESUAI - Vivian Fanny; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2018)
The emerging of entertainment development in Indonesia, increasing number of tourists is one aspect for the world entertainment competition. The increasing insistence and urge in the world of entertainment making the business perform a variety of ways in order to survive and able to compete in the competition. One of the example is the dolphins entertainment, they do a lot of tricks and do interact directly to human. Apart from all the entertainment that we get as the consumer, we do not know how the way dolphins suffer of to do all the orders given for the tricks, to do the direct interaction without injuring humans. All things they went through was a hard painfuly and unpleasant process. As a protected species, the care maintenance and ownership rules should be followed for the sake of the animal welfare. The protection of dolphins entertainment considered as important and should be monitored according the rules to avoid animal abuse.